Recent Progress of Nanomedicine and Targeted Drug Delivery for Cancer Treatment - Zhang, Huijie (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Currently, cancer is the second leading cause of death worldwide and is the most complex and challenging disease known to humankind. Due to the complex underlying mechanisms of tumorigenesis and tumor metastasis, as well as the intrinsic limitations of conventional cancer therapies, the effective treatment of cancer remains a great challenge. Novel therapeutic strategies with superior anticancer ability urgently need to be discovered. In recent years, nano-drug delivery systems have been extensively investigated and applied as alternatives to conventional cancer treatments. Cancer nanomedicines aim to achieve the targeted delivery of chemotherapeutic drugs to the tumor site, utilizing strategies such as passive targeting, active targeting and stimuli-triggered drug release, while simultaneously decreasing drug accumulation in normal tissues, which together lead to improved therapeutic efficacy and reduced side effects. Currently, several cancer nanomedicines are in regular use, and several others are in various stages of development.This Special Issue will highlight recent progress in the development of novel nanomedicines and targeted drug delivery systems for cancer therapy.